Cortical stimulation in pharmacoresistant focal epilepsies - Ellrich, Jens (Bioelectronic Medicine, 2020)
Pharmacoresistance and adverse drug events designate a considerable group of patients with focal epilepsies that require alternative treatments such as neurosurgical intervention and neurostimulation. Electrical or magnetic stimulations of cortical brain areas for the treatment of pharmacoresistant focal epilepsies emerged from preclinical studies and experience through intraoperative neurophysiological monitoring in patients. Direct neurostimulation of seizure onset zones in neocortical brain areas may specifically affect neuronal networks involved in epileptiform activity without remarkable adverse influence on physiological cortical processing in immediate vicinity. Noninvasive low-frequency transcranial magnetic stimulation and cathodal transcranial direct current stimulation are suggested to be anticonvulsant; however, potential effects are ephemeral and require effect maintenance by ongoing stimulation. Invasive responsive neurostimulation, chronic subthreshold cortical stimulation, and epicranial cortical stimulation cover a broad range of different emerging technologies with intracranial and epicranial approaches that still have limited market access partly due to ongoing clinical development. Despite significant differences, the present bioelectronic technologies share common mode of actions with acute seizure termination by high-frequency stimulation and long-term depression induced by low-frequency magnetic or electrical stimulation or transcranial direct current stimulation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Adherence; Anticonvulsant; Chronic subthreshold cortical stimulation; Epicranial cortical stimulation; Long-term depression; Neuromodulation; Responsive neurostimulation; Seizure; Transcranial direct current stimulation; Transcranial magnetic stimulation